A taxonomy of risk‐associated alternative health practices: A Delphi study. (26th May 2021) - Garrett, Bernie; Caulfield, Timothy; Murdoch, Blake; Brignall, Matt; Kapur, Atul Kumar; Murphy, Susan; Nelson, Erin; Reardon, Jillian; Harrison, Mark; Hislop, Jonathan; Wilson‐Keates, Barbara J.; Anthony, Joseph; et al.
Abstract: Defining alternative health care and the recording of associated adverse events and harm remains problematic. This Canadian study aimed to establish and classify risk‐associated alternative health practices in a Delphi study undertaken with an interdisciplinary panel of 17 health experts in 2020. It provides a new functional definition of alternative health care and an initial taxonomy of risk‐associated alternative health care practices. A number of risk‐associated practices were identified and categorized into general practices that conflict with biomedical care or largely untested therapies, alternative beliefs systems, physical manipulative alternative therapies, and herbal and nutritional supplements. Some risk significant harms including major physical injuries or even death. The lack of systematic methods for recording adverse events in alternative health care makes establishing the frequency of such events challenging. However, it is important that people engaging with alternative health care understand they are not necessarily risk‐free endeavours, and what those risks are.